Palynology as a predictive tool in archaeology - Whittington, Graeme; Edwards, Kevin J (Proceedings of the Society of Antiquaries of Scotland, 1995)
Considers the depth and varied nature of palynological data and suggests its use to pose and isolate problems for archaeological investigation rather than be used only as a post-excavation study.